Character association and path analysis in brinjal (Solanum melongena) for yield and yield attributes - AHMED, N; SINGH, S R; LAL, S (The Indian Journal of Agricultural Sciences, 2013)
Character association and path analysis in thirty five genotypicaly diverse indigenous genotypes of brinjal were studied at experimental farm of Central Institute of Temperate Horticulture, Srinagar during year 2009-2010 for eight important characters. The phenotypic and genotypic association of fruit yield was significantly positive with number of fruits/plant, fruit weight and fruit width, whereas plant height, plant spread, number of primary branches and fruit length was non-significantly negatively associated. The genotypic path coefficient revealed that highest positive direct effect (0.700) on fruit yield followed by number of fruits/plant (0.653), plant spread ( 0.053), fruit width (0.052), fruit length (0.030), whereas plant height (– 0.153) showed negative direct effects on fruit yield/plant (kg). Overall the path analysis confined that direct effect of fruit weight, number of fruits/plant, plant spread, fruit width, fruit length and number of primary branches, whereas indirect effect of plant height should be considered simultaneously for amenability in fruit yield of brinjal.